(untitled) (Global Journal of Science Frontier Research, 2023)
Introduction There are times when crises provide more eloquent warnings about unattended problems than all discourses and learned studies The crisis detonated almost 15 years ago by the gas supply cutoff from Argentina awakened Chile to its perilous vulnerability resulting from its growing and excessive dependence on a single source of energy supply This situation also triggered the opportunity to start addressing emerging issues particularly environmental concerns To this end a simple benchmarking exercise was undertaken to enable Chilean power sector stakeholders to learn from what other countries have done in their energy programs in terms of their i impact or results ii all-in costs and iii required institutional arrangements for implementation The results were eye-opening Whereas countries like Germany embarked on an ambitious recasting of their energy matrix others followed a more gradualist and organic approach to increase their share of renewables The former approach required a solid top-down and disciplined investment effort resulting in a significant change in the energy matrix though at a major cost and increased energy risks which became evident early on the Ukrainian war when gas supplies were significantly curtailed triggering an important energy crisis There were others that acted more gradually and hedging through some degree of diversification the risks of misjudging energy demand forecasts